Society & counselling practices - Mohamed, Othman (Universiti Putra Malaysia Press, 2012)
The initial inception of Society and Counselling Practices was conceived in 2005 upon the author’s Inaugural Speech as Professor of Guidance and Counselling at Universiti Putra Malaysia. The ideation evolved into a comprehensive holistic essays connecting the author’s academic research findings, innovative ideation on guidance and counselling theoretical construction works, and reconstruction of research papers presented at international conferences. The essays duly captured in various chapters addressed a repertoire of education,counseling and mental health issues very close to the author’s academic writing interest.